Peran Media Sosial Instagram dan Kesadaran Merek dalam Mempengaruhi Keputusan Pembelian Produk Oatside di Jakarta - Brandinie, Morryessa; Natasya, Verent (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
The growing public awareness of healthy living has encouraged many manufacturers to develop and offer healthier products. Plant-based food and beverage products are one example. Oatside is a plant-based milk drink brand made from oat starch. Oatside was launched in 2022 and actively markets itself on Instagram, gaining a large following in Indonesia, even surpassing the number of followers of other oat milk brands. The goal of this research was to analyze the influence of Instagram social media marketing and brand awareness on Oatside purchasing decisions in the Special Region of Jakarta. The variables used in this study were social media marketing and brand awareness as independent variables, and the dependent variable is defined as purchase decisions . Data were collected from 113 respondents and analyzed using multiple linear regression. Both independent variables showed partially and simultaneously showed a significant positive impact on purchasing decisions, with a joint contribution of 67.3%. Therefore, it can be concluded that Instagram marketing and brand awareness play a significant role in driving Oatside purchases.